Energy performance improvement of a new hybrid PV/T Bi-fluid system using active cooling and self-cleaning: Experimental study. (5th January 2021) - Lebbi, Mohamed; Touafek, Khaled; Benchatti, Ahmed; Boutina, Lyes; Khelifa, Abdelkrim; Baissi, Mohamed Taher; Hassani, Samir
Highlights: A new hybrid PV/T Bi-fluid system has been designed and experimentally tested. Self-cleaning and active cooling process are combined in a single mechanism. The hybrid system improves ηel by up to 5.7% compared to PV reference panel. The T PV, a v g in the hybrid system has been decreased by 15 °C. Average daily energy and exergy efficiency are 85.3% and 14.7%, respectively. Abstract: The operating temperature rise and the dust accumulation on the front side of solar panels especially in arid and semi-arid desert areas is a major issue that causes low performance and damage to photovoltaic cells. This experimental investigation aimed to improve the solar panel electrical performance mounted in new hybrid system PV/T Bi-fluid that combines both active cooling and self-cleaning technique simultaneously. This new hybrid system was actively cooled from the backside of the PV module by forced air circulation, while its front side was cooled and cleaned by flowing water. The impact of the operating temperature and global solar radiation intensity on the PV module output voltage, electrical current, electrical power output, and electrical efficiency was evaluated experimentally. Experimental results showed a decreasing linear relationship between electrical efficiency and the increase in PV module's temperature i.e. reference case without cooling. Up to 15 °C was the average temperature decrease observed in the PV module mounted in the new hybrid system, compared to the reference case. Under the same operating conditions, and at the peak of the global solar irradiation i.e. G = 650 W/m 2, an improvement of about 5.7% in electrical efficiency compared to the reference case was obtained. The average overall energy efficiency was found to be 85.3%, while the average exergy efficiency was roughly 14.7%. Several correlations have been proposed for calculation of electric current intensity, electrical energy output, and electrical efficiency, as a function of the average PV module temperature or global solar radiation intensity. A comparison between the reference case and the new hybrid PV/T Bi-fluid system was proved that this new hybrid system was very effective to maintain the electrical efficiency of the PV module at its highest record.